Economic Justice in the Perspective of Sharia: Solutions to Facing Social Inequality - Mukarromatul Isnaini; Munir Is'adi; Ahmadiono Ahmadiono (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the concept of economic justice from a sharia perspective and explore its application as a solution to the increasing social inequality in society. Economic justice in Islam is a fundamental principle that emphasizes the fair distribution of resources, protection of vulnerable groups, and equal access to economic opportunities. To achieve these goals, this study uses the Systematic Literature Review (SLR) method, which is a structured and systematic approach to identifying, evaluating, and synthesizing scientific literature relevant to the research topic. This method is used to gain a comprehensive understanding of sharia principles such as monotheism, justice ('adl), balance (tawazun), and social responsibility that are the basis for creating a just economic system. The results of the study show that Islamic economic justice is realized through wealth distribution instruments such as zakat, infaq, shadaqah, and waqf, as well as the prohibition of exploitative economic practices such as usury, gharar, and maysir. The current social and economic inequality is caused by various structural factors, including uneven distribution of assets, educational inequality, and a discriminatory economic system. Therefore, the implementation of a sharia-based economic system is a relevant and applicable solution in overcoming social inequality. This approach has proven effective through the application of models such as Baitul Maal wat Tamwil (BMT), sharia cooperatives, and productive waqf, which are able to build an inclusive, sustainable, and equitable economic system. Thus, sharia economics is not only normative in value, but is also able to answer contemporary socio-economic challenges practically